Key Qualifications in Work and Education
274 p.
Keywords: In today's rapidly changing world a constant renewal of knowledge and skills in every human endeavour can be observed. The characteristics of workers and the jobs that they perform have been attended by technological, social, and political change on a global scale. New forms of employment have made work more mobile to an extent never experienced before. An increasing proportion of workers no longer need come to their employer's job site in order to do their work. The instability of employment is creating a new breed of workers who know how to move efficiently from one job to another. As a consequence workers need flexible qualifications to perform jobs. Key qualifications are the answer! Key qualifications provide the key to rapid and effective acquisition of new knowledge and skills. First, qualifications enable workers to react effectively to, and exercise initiative in, changes to their work. Second, qualifications enable workers to shape their own career in a time of diminishing job security, nowadays frequently defined as `employability'.